Developing Reflection and Collaboration in Translational Medicine Toward Patients and Unmet Medical Needs - Clay, Moira; Hiraki, Linda T.; Lamot, Lovro; Medhat, Basma M.; Sana, Salmaan; Small, Anita R. (Frontiers in Medicine, 2019)
This perspective article aims to highlight the importance of values-driven personal reflection and collaboration for effective translational medicine training. We frame the dilemma in translational medicine and provide an approach for solution emphasizing collaboration and co-creation for innovative change in translational research. We cite the science in transition literature suggesting why personal reflection and a collaborative approach is important. We identify the problem with publication pressures and the bibliometric mindset. We focus on motivation to seek and find results that really matter for patients and individuals to maintain health in the real world. We review how the international EUREKA Institute for Translational Medicine (established in 2007) works with students, to harness their core values and develop personal growth skills to improve their leadership effectiveness, to work towards collaborative gain and potentially more meaningful results for patients and medical needs. We describe how the EUREKA Institute’s unique setting, curriculum and hidden curriculum aspects effectively train program participants. The article highlights creating an immersive safe space, personal reflection, connection, structured brainstorming, group problem solving, collaboration and co-creation to facilitate innovation in translational medicine. The article relates program features to their theoretical underpinnings such as Theory U, Mediation Theory and Strategic Innovation Theory. The six authors from different global regions, ages, career stages, translational research contexts and years of attendance at the EUREKA Institute provide their reflections on training impact. Lessons learned and recommendations for research and application are discussed.